Pharmacokinetics of meloxicam after intravenous, intramuscular and oral administration of a single dose to African grey parrots (Psittacus erithacus). Issue 3 (6th September 2016) - Montesinos, A.; Ardiaca, M.; Gilabert, J. A.; Bonvehí, C.; Oros, J.; Encinas, T.
Abstract : Meloxicam is a nonsteroidal anti‐inflammatory drug commonly used in avian species. In this study, the pharmacokinetic parameters for meloxicam were determined following single intravenous (i.v.), intramuscular (i.m.) and oral (p.o.) administrations of the drug (1 mg/kg·b.w.) in adult African grey parrots ( Psittacus erithacus ; n = 6). Serial plasma samples were collected and meloxicam concentrations were determined using a validated high‐performance liquid chromatography assay. A noncompartmental pharmacokinetic analysis was performed. No undesirable side effects were observed during the study. After i.v. administration, the volume of distribution, clearance and elimination half‐life were 90.6 ± 4.1 mL/kg, 2.18 ± 0.25 mL/h/kg and 31.4 ± 4.6 h, respectively. The peak mean ± SD plasma concentration was 8.32 ± 0.95 μg/mL at 30 min after i.m. administration. Oral administration resulted in a slower absorption ( t max = 13.2 ± 3.5 h; C max = 4.69 ± 0.75 μg/mL) and a lower bioavailability (38.1 ± 3.6%) than for i.m. (78.4 ± 5.5%) route. At 24 h, concentrations were 5.90 ± 0.28 μg/mL for i.v., 4.59 ± 0.36 μg/mL for i.m. and 3.21 ± 0.34 μg/mL for p.o. administrations and were higher than those published for Hispaniolan Amazon parrots at 12 h with predicted analgesic effects.